2018
DOI: 10.1002/mas.21562
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and emergent solutions for LC‐MS/MS based untargeted metabolomics in diseases

Abstract: In the past decade, advances in liquid chromatography-mass spectrometry (LC-MS) have revolutionized untargeted metabolomics analyses. By mining metabolomes more deeply, researchers are now primed to uncover key metabolites and their associations with diseases. The employment of untargeted metabolomics has led to new biomarker discoveries and a better mechanistic understanding of diseases with applications in precision medicine. However, many major pertinent challenges remain. First, compound identification has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
188
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(189 citation statements)
references
References 205 publications
(356 reference statements)
1
188
0
Order By: Relevance
“…Metabolomics which is defined as the study of small molecules (<1000 Da) produced or consumed within biological systems, is a booming-omics field of post-genomic biological research, to investigate the effects of molecules on biological systems, and provides a holistic approach to explore the molecular changes caused by a variety of factors in the entire organism (Newgard, 2017;Jang, Chen, & Rabinowitz, 2018). Metabolites are regarded as more representative of phenotypes because the faster changes than that of genetic materials, to indicate the current physiological events (Cui, Lu, & Lee, 2018). In essence, metabolomics has been widely employed by the scientific community, and considered to be an extensively used technique for biomarker identification (Guijas et al, 2018a;Mayerle et al, 2018), disease diagnosis (Costello, 2018;Grasso, 2018), novel drug discovery (Wishart, 2016), drug mechanism study (Matsui et al, 2017;Beyer et al, 2018), drug safety, and toxicology evaluation , because it provides highly reliable and repeatable results.…”
Section: Metabolomics: An Overviewmentioning
confidence: 99%
“…Metabolomics which is defined as the study of small molecules (<1000 Da) produced or consumed within biological systems, is a booming-omics field of post-genomic biological research, to investigate the effects of molecules on biological systems, and provides a holistic approach to explore the molecular changes caused by a variety of factors in the entire organism (Newgard, 2017;Jang, Chen, & Rabinowitz, 2018). Metabolites are regarded as more representative of phenotypes because the faster changes than that of genetic materials, to indicate the current physiological events (Cui, Lu, & Lee, 2018). In essence, metabolomics has been widely employed by the scientific community, and considered to be an extensively used technique for biomarker identification (Guijas et al, 2018a;Mayerle et al, 2018), disease diagnosis (Costello, 2018;Grasso, 2018), novel drug discovery (Wishart, 2016), drug mechanism study (Matsui et al, 2017;Beyer et al, 2018), drug safety, and toxicology evaluation , because it provides highly reliable and repeatable results.…”
Section: Metabolomics: An Overviewmentioning
confidence: 99%
“…The already-mentioned studies [18][19][20][21][22] with 3D cultures involving LC-MS-based metabolomics workflows, including lipidomics and fluxomics applications utilized washing of the samples and organic solvents (methanol, acetonitrile) with an aqueous proportion for extraction, mostly in cold state. To the best of our knowledge, a thorough evaluation of 3D cancer cell models is still lacking.…”
Section: Speeding Up the Sample Preparationmentioning
confidence: 99%
“…One of the biggest hopes in cancer metabolomics is the discovery of molecular signatures with predictive power in cancer therapy [16]. As a consequence of this renewed interest in metabolism, dedicated workflows were introduced, addressing the needs of preclinical and clinical studies [17][18][19]. Cancer cell model studies required the development and validation of multi-step sample preparation protocols [20].…”
Section: Introductionmentioning
confidence: 99%
“…Glycocholic acid is a secondary bile acid, and particularly high levels of bile acids have been implicated in the pathogenesis of liver diseases 19 . One study suggested that glycocholic acid and taurochenodeoxycholic acid 18 can be used as phenotypic biomarkers in cholangiocarcinoma 20 . In this study, glycocholic acid in plasma was observed to be positively correlated with pancreatic cancer, suggesting that bile acids might also be closely associated with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%